Um fantasma assombra a ciência, o fantasma da pirataria: análise do uso e das representações de meios ilegais de acesso à literatura científica na CONICET (Argentina) - Zukerfeld, Mariano (2021)
This article presents the results of a survey carried out among researchers from Argentina on the different types of access to scientific literature, the motivations for using the illegal via, representations on legality and moral correctness in access to scientific articles, and the link between productivity and access vias. It offers empirical evidence of a massive and widespread use of illegal access to scientific literature among respondents. The most notable finding is, on the one hand, that the use of the illegal via of access does not supplant, but rather coexists with the use of legal vias. On the other hand, there is a remarkable disconnection between the representation regarding legality and correctness on the access and dissemination of scientific literature protected by copyright. Third, the motivations that explain the massive use of illegal vias combine practical and evaluative aspects, such as the impossibility of accessing in another way and the ease of use in opposition to legal services and the rejection of the publishing business around scientific literature.